The characteristics of diabetic residents in European nursing homes: results from the SHELTER study - Szczerbińska, Katarzyna; Topinková, Eva; Brzyski, Piotr; van der Roest, Henriëtte G; Richter, Tomáš; Finne-Soveri, Harriet; Denkinger, Michael D; Gindin, Jacob; Onder, Graziano; Bernabei, Roberto (Journal of the American Medical Directors Association, 2015)
OBJECTIVES: The objectives of this study were to describe the prevalence of diabetes mellitus (DM) in European nursing homes (NHs), and the health and functional characteristics of diabetic residents (DMR) aged 60 years and older. DESIGN: Between 2009 and 2011, the Services and Health for Elderly in Long TERm care (SHELTER) project, a 12-month prospective cohort study, was conducted to assess NH residents across different health care systems in 7 European countries and Israel. METHODS: The study included 59 NHs in 8 countries with a total of 4037 residents living in or admitted to a NH during the 3-month enrollment period. The multidimensional InterRAI instrument for Long-Term Care Facilities (InterRAI-LTCF) was used to assess health and functional status among residents. Descriptive statistics and linear, ordinal, and logistic regression were used to perform the analyses. RESULTS: We found a 21.8% prevalence of DM among NH residents. Residents with DM (DMRs) were significantly younger compared with non-DMRs (82.3, SD ± 7.7; 84.6, SD ± 8.4; P < .001). DMRs were more frequently overweight or obese, and presented more often with ischemic heart disease, congestive heart failure, hypertension, and stroke than residents without DM. DMRs also took more drugs, had pressure ulcers (PU) or other wounds more often, and more frequently had urinary incontinence (UI); they also reported worse self-perceived health. DM independently of other factors increased risk of PU occurrence (odds ratio 1.38; 95% confidence interval [CI] 1.02-1.86; P = .036) and decreased probability of higher pain scores (B = -0.28; 95% CI -0.41 to -0.14; P < .001). DM was not associated with ADL dependency, cognitive impairment, and depression in NH residents. CONCLUSION: Prevalence of DM in European NH residents is comparable to US national NH surveys, and to UK and German NH data based on glucose-level testing. DMRs compared with non-DMRs have more comorbid conditions, and a particularly higher incidence of cardiovascular diseases and obesity, PU, and severe UI. DMRs should be regarded as a specific group of residents who require an interdisciplinary approach in medical and nursing care.
Keywords: Sex Distribution; logistické modely; Female; Europe; Prevalence; rozložení podle pohlaví; multivariační analýza; Quality of Life; Geriatric Assessment; ženské pohlaví; Linear Models; Logistic Models; Multivariate Analysis; diabetes mellitus; kvalita života; lidé; Evropa; geriatrické hodnocení; Aged, 80 and over; míra přežití; lineární modely; Homes for the Aged; domovy pro seniory; stupeň závažnosti nemoci; Long-Term Care; prognóza; Nursing Homes; kohortové studie; neparametrická statistika; prevalence; Cohort Studies; Age Distribution; prospektivní studie; Male; Aged; Prospective Studies; dlouhodobá péče; věkové rozložení; Diabetes Complications; Prognosis; Survival Rate; Diabetes Mellitus; lidé středního věku; Statistics, Nonparametric; senioři nad 80 let; senioři; mužské pohlaví; Severity of Illness Index; komplikace diabetu; Middle Aged; pečovatelské domovy; Humans